Performance Budgeting in Poland An OECD Review - Hawkesworth, Ian (OECD Publishing, 2011)
Poland currently has a traditional budget system that is primarily based on organisational units and control of inputs. But Poland is in the process of introducing a new budget system, the performance-based budgeting system, in order to improve public finance management and strengthen allocative and operational efficiency, multi-year budgeting, and transparency and accountability. Poland faces hard choices on how to harness the advantages of performance management while minimising the costs in terms of organisational capacity and funding. This article assesses the reform process to date, examines cross-cutting institutional, technical, and strategic issues, and provides a series of recommendations for each stage of the budget process: budget preparation, approval and execution, and reporting, accounting and audit. JEL classification: H500, H610, H830 Keywords: Poland, budget process, performance budgeting system, performance-based budget, PBB, public finance management, allocative efficiency, operational efficiency, multi-year budgeting, transparency, accountability